THE EFFECT OF PLAYING ONLINE GAMES ON THE LEARNING ACHIEVEMENT OF CLASS VIII STUDENTS IN THE SUBJECT OF ISLAMIC RELIGIOUS EDUCATION AT SMP NEGERI 1 MAPPAKASUNGGU, TAKALAR REGENCY (International Conference on Social and Islamic Studies, 2022)
This thesis aims to; 1) describe the use of online games among Class VIII students at SMP Negeri 1 Mappakasunggu, Takalar Regency; 2) describe the learning achievements of class VIII students in the Islamic Religious Education subject at SMP Negeri 1 Mappakasunggu, Takalar Regency; 3) analyze the effect of playing online games on the learning achievement of Class VIII students in the subject of Islamic Religious Education at SMP Negeri 1 Mappakasunggu, Takalar Regency. This type of research is ex post facto quantitative with a simple linear regression research design. This research was conducted at SMP Negeri 1 Mappakasunggu. The population in this study were 146 class VIII students at SMP Negeri 1 Mappakasunggu. While the sample in this study were 29 people using a simple random sampling method. The data were obtained through a questionnaire instrument, the data analysis technique used was descriptive statistics and inferential analysis. The results showed that the use of online games was in the moderate category, which was 33%, while the learning achievement of students in class VIII Islamic religious education at SMP Negeri 1 Mappakasunggu, Takalar Regency, was moderate, namely 84.5%. From the calculation results obtained = 3.38 while = for a significant level of 0.05%. Because it is greater than, it can be concluded that it is rejected and accepted. This means that there is an effect of playing online games on the learning achievement of class VIII students in the Islamic Religious Education subject at SMP Negeri 1 Mappakasungu, Takalar Regency. The implications of this research are 1) For the school to activate extracurricular activities in order to divert students from doing online game activities; 1) For parents to participate in controlling children's activities both in the public environment, school and family environment; 3) For people who have online game facilities to be used by school children, they should be effective, of good quality, include and enforce special rules for students who are still in school uniforms or carrying school bags to be prohibited from entering the online game area.